E-003 Initial experience with a 'timeout' designed for neuroendovascular procedures. (16th November 2010) - Wells, K; Kapadia, S; Cantrell, B; Keigher, K; Lopes, D; Chen, M
Abstract : Introduction: Morbidity and mortality as a result of medical errors has become a significant health problem. As part of a national patient safety goal initiative, almost all medical centers have adopted measures to decrease the incidence of medical errors. In order to improve communication among members of the surgical team, a preoperative checklist is done prior to initiating any procedure (time out). The neuroendovascular patient undergoing an intervention such as cerebral aneurysm coiling and/or stenting, arteriovenous malformation embolization and carotid stenting presents unique challenges compared with body interventions or open neurosurgery cases. Some of these challenges include assessment of patient kidney function, contrast allergy, femoral/pedal pulses, need for ASA/Plavix and humanitarian device exemption (HDE) consents. The purpose of this study was to develop a 'time out' customized to neuroendovascular patients and test it in a clinical setting. Materials and methods: We listed the most important safety factors involving neuroendovascular interventions and compared them to the standard open surgery 'time out' checklist. A specific neuroendovascular checklist was developed. We then in-serviced the staff of the neuro-angio suite which included six registered nurses, four radiology technologists and two endovascular surgeons to institute the preoperative checklist. The following is an abbreviated form of the neuroendovascular time out we implemented: What patient do we have? What procedure are we doing? Do we need any HDE/special consents (Enterprise, Neuroform, Wingspan, Research)? What is the assessment of access site and marking? Is the patient positioned correctly? Are there any precautions based on status or meds? Are ASA and Plavix required for the procedure; or other special medications? Are irrigation fluids required and available? Do we require any special implants, equipment, films? If so are they available? Are any antibiotics required? Is DVT prophylaxis indicated? After 3 months of clinical application of the neuroendovascular time out at RUSH University, the team was asked to respond to a self-assessment questionnaire. Results: The neuroendovascular time out was applied in 152 cases over 3 months. In all cases the time out was completed before the procedure initiated. The answers to each time out were documented and incorporated to the patient's electronic medical record. The answers from the self-assessment questionnaire were obtained from all the participating members of the endovascular team. The results revealed great acceptance to the concept of time out and 12/12 questionnaires agreed that the customization was more relevant to neuroendovascular patients. There was also unanimous opinion that the neuroendovascular time out has increased safety for our patients undergoing procedures. Conclusion: The neuroendovascular time out is more relevant to cerebrovascular patients and proved to be valuable in a clinical setting.